(untitled) (Research, Society and Development, 2022)
The Electric Stimulation (ES) has been shown to have beneficial effects in wound healing. It is important to assess the effects of ES on the healing of skin wounds in order to guarantee the optimal clinical practice. Objective: This review article aimed to evaluate the importance of ES in wound healing by the scarce literature and the lack of consensus among the treatments. Methods: A search in the electronic databases PubMed, Lilacs and SciELO was performed using the keywords "Stimulation", "wound healing" and "Wistar". Inclusion criteria consisted of studies with Wistar animals treated with ES, published in English or Portuguese languages ​​in the period between 1966 and 2021. The data from the study results were determined by morphology. Results: seven studies were selected and all pointed to the importance of the electrical stimulation mode to accelerate wound healing. Although there is a considerable amount of research on the effect of ES as an adjunct in the treatment of various pathologies, a small amount and a great variability in the parameters used is observed in the healing process. There is also a consensual concern about the need for standardization of doses, as each author defends its applicability. Best results are achieved when using the micro amperage isolated or associated in the treatment of wound healing. Conclusion: Further studies are needed to corroborate with the padronization of the electrical stimulation in the cutaneous wound healing process.